Pengaruh Rasio Keuangan Terhadap Return Saham Pada Perusahaan Yang Tercantum Dalam Jakarta Islamic Index - M Akbar Fadhilah Akbar Fadhilah; Wahyu Dwi Warsitasari Warsitasari (Jurnal Riset Akuntansi, 2023)
The purpose of this research is to find out how the stock returns of companies listed in the Jakarta Islamic Index are influenced by financial ratios such as the Liquidity Ratio, Activity Ratio, Profitability Ratio, Solvency Ratio, and Market Value Ratio. Quantitative approach and type of associative research are used as research methods. This study used secondary data and used panel data regression analysis with the help of Microsoft Excel and Eviews 9. A purposive sampling technique was used to select 16 companies listed on the Jakarta Islamic Index between 2017 and 2021 to be used as research samples. The results of the study show that simultaneously the Liquidity Ratio, Activity Ratio, Profitability Ratio, Solvency Ratio and Market Value Ratio have a significant effect on stock returns. While partially the Liquidity Ratio, Activity Ratio and Profitability Ratio do not have a significant effect on stock returns. Then the Solvency Ratio has a negative and significant effect on stock returns, and the Market Value Ratio has a positive and significant effect on stock returns.